2016
DOI: 10.3389/fmicb.2016.01305
|View full text |Cite
|
Sign up to set email alerts
|

Relevant Genes Linked to Virulence Are Required for Salmonella Typhimurium to Survive Intracellularly in the Social Amoeba Dictyostelium discoideum

Abstract: The social amoeba Dictyostelium discoideum has proven to be a useful model for studying relevant aspects of the host-pathogen interaction. In this work, D. discoideum was used as a model to study the ability of Salmonella Typhimurium to survive in amoebae and to evaluate the contribution of selected genes in this process. To do this, we performed infection assays using axenic cultures of D. discoideum co-cultured with wild-type S. Typhimurium and/or defined mutant strains. Our results confirmed that wild-type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
53
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 83 publications
2
53
0
Order By: Relevance
“…Autophagy and related processes have emerged as important innate immune defense mechanisms against intracellular bacterial infections, and several pathogens, including Salmonella, are known to have evolved mechanisms to counteract the host autophagy response [4][5][6][8][9][10][11][12][74][75][76]. Macrophages are the key cell type responsible for dissemination of Salmonella during systemic typhoid disease.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy and related processes have emerged as important innate immune defense mechanisms against intracellular bacterial infections, and several pathogens, including Salmonella, are known to have evolved mechanisms to counteract the host autophagy response [4][5][6][8][9][10][11][12][74][75][76]. Macrophages are the key cell type responsible for dissemination of Salmonella during systemic typhoid disease.…”
Section: Discussionmentioning
confidence: 99%
“…We anticipated that these mutants would be contained in a vacuolar compartment unable to support the intracellular survival of the pathogen. Therefore, we performed infection assays in D. discoideum under conditions that have been described by our group (27, 28) ( Figure 7 ). We found that the number of internalized bacteria was similar between the different strains ( Figure 7A ), indicating that the deletion of genes sopB and sifA does not affect the uptake of S .…”
Section: Resultsmentioning
confidence: 99%
“…To be able to understand this wide range of hosts and the diversity of virulence strategies, there is a need for establishing more models for studying mechanisms required for infecting diverse hosts. is was successfully accomplished using D. discoideum as a host model to study the pathogenesis of Klebsiella, Legionella, Pseudomonas, and Salmonella infections [21][22][23]36].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to limited tools and antigens to study intracellular lifestyle in free-living amoeba, such as A. castellanii and H. vermiformis, D. discoideum has been used as a model organism to study phagocytosis, cell motility, and virulence factors for many bacterial pathogens, such as Pseudomonas, Legionella, Mycobacterium, Salmonella, and Klebsiella [18][19][20][21][22][23]. Dictyostelium has been established as a model organism for studying the life cycle of the fish pathogen, F. noatunensis, but it has not been established for studying the strains of Francisella that cause the disease in humans [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation